(10 intermediate revisions by 2 users not shown)
Line 1: Line 1:
[[Category:slecture]]
+
[[Category:bonus point project]]
 
[[Category:ECE438Fall2014Boutin]]  
 
[[Category:ECE438Fall2014Boutin]]  
 
[[Category:ECE]]
 
[[Category:ECE]]
 
[[Category:ECE438]]
 
[[Category:ECE438]]
[[Category:signal processing]]
+
[[Category:signal processing]]
 +
[[Category:z transform]]
 +
[[Category:tutorial]]
  
 
<center>
 
<center>
==Inverse Z Transform *under construction*==
+
==Inverse Z Transform==
 +
Student project for [[2014_Fall_ECE_438_Boutin|ECE438 Fall 2014]]
 
</center>
 
</center>
 
+
----
 
+
----
 
'''Introduction'''
 
'''Introduction'''
 
+
The Z Transform is the generalized version of the DTFT. You can obtain the Z Transform from the DTFT by replacing <math>e^{j\omega}</math> with <math> re^{j\omega} </math> which is equivalent to z. The The DTFT is equal to the Z Transform when <math>|z| =1 </math>  
The Z Transform is the generalized version of the DTFT. You can obtain the Z Transform from the DTFT by replacing <math>e^{j\omega}</math> with <math> re^{j\omega} = z </math>. The The DTFT is equal to the Z Transform when <math>|z| =1 </math>  
+
  
 
<math>
 
<math>
Line 30: Line 32:
 
\end{align}
 
\end{align}
 
</math>
 
</math>
 
+
----
 
'''Region of Convergence (ROC)'''
 
'''Region of Convergence (ROC)'''
 
+
The ROC determines the region on the Z Plane where the Z Transform converges. The ROC depends solely on the 'r' value that is contained in 'z'. The ROC is one of three cases;
The ROC determines the region on the Z Plane where the Z Transform converges. The ROC depends solely on the 'r' value that is contained in 'z'. The ROC is always one of three cases;
+
:1. The ROC starts from a circle centered at the origin and fills in toward the origin
:1. The ROC starts from a circle centered at the origin and extends outward to infinity
+
:2. The ROC starts from a circle centered at the origin and extends outward to infinity
:2. The ROC starts from a circle centered at the origin and fills in toward the origin
+
:3. The ROC is the space in between two circles centered at the origin.
:3. The ROC is the space in-between two circles centered at the origin.
+
If the ROC includes the unit circle then the DTFT converges for that function if it is not included, then it does not.
If the ROC includes the unit circle then the DTFT exists for that function if it is not included, then it does not exist.
+
  
 
<math>
 
<math>
Line 46: Line 47:
 
</math>
 
</math>
  
""II. Example Problems of the Inverse Z Transform""
+
The ROC is determined when preforming Z transforms and is given when preforming inverse Z transforms.
 +
----
 +
'''Solving an inverse Z Transform'''
 +
To find the Inverse Z transform of signals use manipulation then direct Inversion. Do not use formula directly!
  
 +
The Infinite Geometric Series formula is used in most problems involving Inv. Z transform.
  
:We will find the Inverse Z transform of various signals by manipulation and then using direct Inversion.
+
<math>
:On the first example we will go slowly over each step.
+
\begin{align}
 +
\text{Infinite Geometric Series: }
 +
X(z) &= \sum_{n=-\infty}^{\infty} (a)r^{n} u[n]\\
 +
      &= \sum_{n=0}^{\infty} (a)r^{n}\\
 +
      &= \frac{a}{1-r}\\
 +
\end{align}
 +
</math>
 +
 
 +
it can be seen that this general form is already starting to look like that of the Z Transform, with some change of variables we can manipulate this equation to be that of a Z transform and then by comparison find the inverse z transform.
 +
----
 +
'''Examples'''
  
 
Ex. 1 Find the Inverse Z transform of the following signal  
 
Ex. 1 Find the Inverse Z transform of the following signal  
Line 56: Line 71:
 
<math>X(z)=\frac{1}{1-z}, \text{ ROC } |z|<1 </math>
 
<math>X(z)=\frac{1}{1-z}, \text{ ROC } |z|<1 </math>
  
::note: It is important to realize that we are not going to try to use the direct formula for an inverse Z transform, Instead our approach will be to manipulate the signal so that we can directly compare it with the Z transform equation and by inspection obtain the Inverse Z transform.
+
:notice: ROC is type 1
 +
Solution
  
:First we need to manipulate the given ROC inequality to be in the following form, with 'A' being some expression that contains z
+
<math>
<center><math>|A| < 1</math></center>
+
\begin{align}
 
+
X(x) &= \frac{1}{1-z}\\
:In this case this is already satisfied with
+
      &= \sum_{n=0}^{\infty} 1(z^{n}) \text{  if } |z| < 1\\
<center><math>A = z</math></center>
+
      &= \sum_{n=-\infty}^{\infty} z^{n} u[n]\\
 
+
      &\text{let }k = -n\\
:Then we need to manipulate the given signal to be in the following form, B is just some expression that is the result of adjusting the equation (in this case B = 1)
+
      &= \sum_{k=-\infty}^{\infty} z^{-k} u[-k]\\
<center><math>X(z)=B\frac{1}{1-A}</math></center>
+
      &= \sum_{k=-\infty}^{\infty}u[-k] z^{-k}\\
 
+
      &\text{By comparison with the Z Transform definition..}\\
:Using a infinite Geometric sum we can obtain following...
+
x[n] &= u[-n]\\
 
+
\end{align}
<center><math>X(z) = \sum_{n=0}^{\infty} 1(z^{n}) = \sum_{n=-\infty}^{\infty} z^{n} u[n]</math></center>
+
</math>
 
+
<center><math>\text{let } k = -n \text{ then, } X(z) = \sum_{k=-\infty}^{\infty} z^{-k} u[-k]= \sum_{k=-\infty}^{\infty}u[-k] z^{-k}</math></center>
+
 
+
: By comparison with the Z Transform definition, we can determine <math> x[n] </math>
+
 
+
<center><math>x[n] = u[-n]</math></center>
+
  
 
Ex. 2 Find the Inverse Z transform of the following signal  
 
Ex. 2 Find the Inverse Z transform of the following signal  
Line 81: Line 91:
 
<math>X(z)=\frac{1}{1-z}, \text{ ROC } |z|>1 </math>
 
<math>X(z)=\frac{1}{1-z}, \text{ ROC } |z|>1 </math>
  
:First we need to manipulate the given ROC inequality to be in the following form, with 'A' being some expression that contains z
+
:notice: ROC is type 2
<center><math>|A| < 1</math></center>
+
Solution
  
:In this case
+
<math>
<center><math>A = \frac{1}{z}</math></center>
+
\begin{align}
 +
X(z) &= \frac{1}{1-z} \\
 +
      &= \frac{1}{z} \frac{1}{1-(-\frac{1}{z})}\\
 +
      & \text{Using a infinite Geometric series...}\\
 +
      &= \sum_{n=0}^{\infty} (\frac{-1}{z})^{n}\frac{1}{z} \text{  if } |-\frac{1}{z}| < 1\\
 +
      &=  \sum_{n=0}^{\infty}(-1)^{n} z^{-n-1} \\
 +
      &=  \sum_{n=-\infty}^{\infty} (-1)^{n} z^{-n-1} u[n]\\
 +
      &\text{ let } k=n+1 \\
 +
      &=  \sum_{k=-\infty}^{\infty}(-1)^{k-1} z^{-k} u[k-1] \\
 +
      &=  \sum_{k=-\infty}^{\infty} (-1)^{k-1} u[k-1] z^{-k}\\
 +
      &\text{By comparison with the Z Transform definition...}\\
 +
x[n] &=(-1)^{n-1} u[n-1]\\
 +
\end{align}
 +
</math>
  
:Manipulate the given signal
+
Ex. 3 Find the Inverse Z transform of the following signal  
<center><math>X(z)=\frac{1}{1-z} = \frac{1}{z} \frac{1}{1-(-\frac{1}{z})}</math></center>
+
  
:Using a infinite Geometric sum we can obtain
+
<math>X(z)=\frac{z}{1-5z}, \text{ ROC } |z|<\frac{1}{5} </math>
  
<center><math>X(z) =  \sum_{n=0}^{\infty} (\frac{-1}{z})^{n}\frac{1}{z} =  \sum_{n=0}^{\infty}(-1)^{n} z^{-n-1} =  \sum_{n=-\infty}^{\infty} (-1)^{n} z^{-n-1} u[n]</math></center>
+
:notice: ROC is type 1
 +
Solution
  
<center><math> \text{ let } k=n+1, \text{ then } X(z) = \sum_{k=-\infty}^{\infty}(-1)^{k-1} z^{-k} u[k-1] = \sum_{k=-\infty}^{\infty} (-1)^{k-1} u[k-1] z^{-k}</math></center>
+
<math>
 
+
\begin{align}
:By comparison with the Z Transform definition, we can determine <math> x[n] </math>
+
X(x) &= \frac{z}{1+5z}\\
 
+
      &= \frac{z}{1-(-5z)}\\
<center><math>x[n] = (-1)^{n-1} u[n-1]</math></center>
+
      &= \sum_{n=0}^{\infty} z(-5z^{n}) \text{  if } |z| < \frac{1}{5}\\
 +
      &= \sum_{n=-\infty}^{\infty} (-5)^{n}z^{n+1} u[n]\\
 +
      &\text{let }k = -n-1\\
 +
      &= \sum_{k=-\infty}^{\infty} (-5)^{-k-1}z^{-k} u[-k-1]\\
 +
      &= \sum_{k=-\infty}^{\infty}(-5)^{-k-1}u[-k-1] z^{-k}\\
 +
      &\text{By comparison with the Z Transform definition...}\\
 +
x[n] &= (-5)^{-n-1}u[-n-1]\\
 +
\end{align}
 +
</math>
  
 
Ex. 4 Find the Inverse Z transform of the following signal  
 
Ex. 4 Find the Inverse Z transform of the following signal  
Line 104: Line 135:
 
<math>X(z)=\frac{1}{1-2z}, \text{ ROC } |2z|>1 </math>
 
<math>X(z)=\frac{1}{1-2z}, \text{ ROC } |2z|>1 </math>
  
:Manipulate the given signal
+
:notice: ROC is type 2
 +
Solution
  
<center><math>X(z)=\frac{1}{1-2z} = \frac{1}{2z} \frac{1}{1-(-\frac{1}{2z})}</math></center>
+
<math>
 +
\begin{align}
 +
X(z) &= \frac{1}{1-2z}\\
 +
      &= \frac{1}{2z} \frac{1}{1-(-\frac{1}{2z})}\\
 +
      &= \sum_{n=0}^{\infty} (\frac{-1}{2z})^{n}\frac{1}{2z} \text{  if } |-\frac{1}{2z}| < 1\\
 +
      &= \sum_{n=0}^{\infty} (-2z)^{-n}(2z)^{-1}\\
 +
      &= \sum_{n=-\infty}^{\infty} \frac{1}{2}(-2)^{-n}z^{-n-1} u[n]\\
 +
      &\text{ let } k=n+1\\
 +
      &= \sum_{k=-\infty}^{\infty} \frac{1}{2}(-2)^{-k+1}u[k-1] z^{-k}\\
 +
      &\text{By comparison with the Z Transform definition...}\\
 +
x[n] &= \frac{1}{2}(-2)^{-k+1}u[n-1]\\
 +
\end{align}
 +
</math>
  
:Using a infinite Geometric sum we can obtain
+
Ex. 5 Find the Inverse Z transform of the following signal
  
<center><math>X(z) = \sum_{n=0}^{\infty} (\frac{-1}{2z})^{n}\frac{1}{2z} = \sum_{n=0}^{\infty} (-2z)^{-n}(2z)^{-1}= \sum_{n=-\infty}^{\infty} \frac{1}{2}(-2)^{-n}z^{-n-1} u[n]</math></center>
+
<math>X(z)=\frac{-1}{z^2-4z-5}, \text{ ROC } 1<|z|<5 </math>
  
<center><math> \text{ let } k=n+1, \text{ then } X(z) = \sum_{k=-\infty}^{\infty} \frac{1}{2}(-2)^{-k+1}u[k-1] z^{-k}</math></center>
+
:notice: ROC is type 3
 +
Solution
  
: By comparison with the Z Transform definition, we can determine <math> x[n] </math>
+
<math>
 +
\begin{align}
 +
X(z) &= \frac{-1}{z^2-4z-5}\\
 +
      &\text{ by partial fraction expansion}\\
 +
      &= \Big( \frac{1}{6} \Big)\Big( \frac{1}{z+1}+\frac{1}{5-z} \Big)\\
 +
      & \text{by infinite geometric series}\\
 +
      &= \Big( \frac{1}{6} \Big) \Bigg( \sum_{n=0}^{\infty} (\frac{1}{z})(\frac{-1}{z})^{n} + \sum_{m=0}^{\infty} (\frac{1}{5})(\frac{z}{5})^m \Bigg) \text{  if } 1<|z|< 5\\
 +
      &=\Big( \frac{1}{6} \Big) \Bigg( \sum_{n=-\infty}^{\infty} (-1)^n(z)^{-n-1}u[n] + \sum_{m=-\infty}^{\infty} (5)^{-m-1)}(z)^{m}u[m] \Bigg)\\
 +
      & \text{let } k=n+1, l=-m\\
 +
      &= \Big( \frac{1}{6} \Big) \Bigg( \sum_{k=-\infty}^{\infty} (-1)^{k-1}(z)^{-k}u[k-1] + \sum_{l=-\infty}^{\infty} (5)^{l-1)}(z)^{-l}u[-l] \Bigg)\\
 +
      & \text{using the linearity principle of Z transforms}\\
 +
x[n] &= \frac{1}{6}(-1)^{n-1}u[n-1] + \frac{1}{6} (5)^{n-1)}(z)^{-n}u[-n]
 +
   
 +
\end{align}
 +
</math>
  
<center><math>x[n] = \frac{1}{2}(-2)^{-k+1}u[n-1]</math></center>
+
----
 +
'''Using Matlab to find Inverse Z Transforms'''
 +
[http://www.mathworks.com/help/symbolic/iztrans.html|mathworks.com]
 +
----
 +
'''Additional links'''
 +
*[https://www.youtube.com/watch?v=wG6VUnkrO90|Good instructional video]
 +
*[[Z_Transform_table|Z Transform Pairs and Properties]]
 +
----
 +
'''Questions, Comments'''
 +
-
 +
-
 +
-
 +
----
 +
[[2014_Fall_ECE_438_Boutin|Back to ECE438 Fall 2014]]

Latest revision as of 18:11, 23 February 2015


Inverse Z Transform

Student project for ECE438 Fall 2014



Introduction The Z Transform is the generalized version of the DTFT. You can obtain the Z Transform from the DTFT by replacing $ e^{j\omega} $ with $ re^{j\omega} $ which is equivalent to z. The The DTFT is equal to the Z Transform when $ |z| =1 $

$ \begin{align} \text{DTFT: } X(w) &= \sum_{n=-\infty}^\infty x[n]e^{-j\omega n}\\ \text{Z-Transform: } X(z) &= \sum_{n=-\infty}^\infty x[n]z^{-n}\\ \text{Inv. Z-Transform: } x[n] &= \frac{1}{2\pi j}\oint_{c}X(z)z^{n-1}dz \end{align} $


Region of Convergence (ROC) The ROC determines the region on the Z Plane where the Z Transform converges. The ROC depends solely on the 'r' value that is contained in 'z'. The ROC is one of three cases;

1. The ROC starts from a circle centered at the origin and fills in toward the origin
2. The ROC starts from a circle centered at the origin and extends outward to infinity
3. The ROC is the space in between two circles centered at the origin.

If the ROC includes the unit circle then the DTFT converges for that function if it is not included, then it does not.

$ \begin{align} \text{Remember: } z &=re^{j\omega} \end{align} $

The ROC is determined when preforming Z transforms and is given when preforming inverse Z transforms.


Solving an inverse Z Transform To find the Inverse Z transform of signals use manipulation then direct Inversion. Do not use formula directly!

The Infinite Geometric Series formula is used in most problems involving Inv. Z transform.

$ \begin{align} \text{Infinite Geometric Series: } X(z) &= \sum_{n=-\infty}^{\infty} (a)r^{n} u[n]\\ &= \sum_{n=0}^{\infty} (a)r^{n}\\ &= \frac{a}{1-r}\\ \end{align} $

it can be seen that this general form is already starting to look like that of the Z Transform, with some change of variables we can manipulate this equation to be that of a Z transform and then by comparison find the inverse z transform.


Examples

Ex. 1 Find the Inverse Z transform of the following signal

$ X(z)=\frac{1}{1-z}, \text{ ROC } |z|<1 $

notice: ROC is type 1

Solution

$ \begin{align} X(x) &= \frac{1}{1-z}\\ &= \sum_{n=0}^{\infty} 1(z^{n}) \text{ if } |z| < 1\\ &= \sum_{n=-\infty}^{\infty} z^{n} u[n]\\ &\text{let }k = -n\\ &= \sum_{k=-\infty}^{\infty} z^{-k} u[-k]\\ &= \sum_{k=-\infty}^{\infty}u[-k] z^{-k}\\ &\text{By comparison with the Z Transform definition..}\\ x[n] &= u[-n]\\ \end{align} $

Ex. 2 Find the Inverse Z transform of the following signal

$ X(z)=\frac{1}{1-z}, \text{ ROC } |z|>1 $

notice: ROC is type 2

Solution

$ \begin{align} X(z) &= \frac{1}{1-z} \\ &= \frac{1}{z} \frac{1}{1-(-\frac{1}{z})}\\ & \text{Using a infinite Geometric series...}\\ &= \sum_{n=0}^{\infty} (\frac{-1}{z})^{n}\frac{1}{z} \text{ if } |-\frac{1}{z}| < 1\\ &= \sum_{n=0}^{\infty}(-1)^{n} z^{-n-1} \\ &= \sum_{n=-\infty}^{\infty} (-1)^{n} z^{-n-1} u[n]\\ &\text{ let } k=n+1 \\ &= \sum_{k=-\infty}^{\infty}(-1)^{k-1} z^{-k} u[k-1] \\ &= \sum_{k=-\infty}^{\infty} (-1)^{k-1} u[k-1] z^{-k}\\ &\text{By comparison with the Z Transform definition...}\\ x[n] &=(-1)^{n-1} u[n-1]\\ \end{align} $

Ex. 3 Find the Inverse Z transform of the following signal

$ X(z)=\frac{z}{1-5z}, \text{ ROC } |z|<\frac{1}{5} $

notice: ROC is type 1

Solution

$ \begin{align} X(x) &= \frac{z}{1+5z}\\ &= \frac{z}{1-(-5z)}\\ &= \sum_{n=0}^{\infty} z(-5z^{n}) \text{ if } |z| < \frac{1}{5}\\ &= \sum_{n=-\infty}^{\infty} (-5)^{n}z^{n+1} u[n]\\ &\text{let }k = -n-1\\ &= \sum_{k=-\infty}^{\infty} (-5)^{-k-1}z^{-k} u[-k-1]\\ &= \sum_{k=-\infty}^{\infty}(-5)^{-k-1}u[-k-1] z^{-k}\\ &\text{By comparison with the Z Transform definition...}\\ x[n] &= (-5)^{-n-1}u[-n-1]\\ \end{align} $

Ex. 4 Find the Inverse Z transform of the following signal

$ X(z)=\frac{1}{1-2z}, \text{ ROC } |2z|>1 $

notice: ROC is type 2

Solution

$ \begin{align} X(z) &= \frac{1}{1-2z}\\ &= \frac{1}{2z} \frac{1}{1-(-\frac{1}{2z})}\\ &= \sum_{n=0}^{\infty} (\frac{-1}{2z})^{n}\frac{1}{2z} \text{ if } |-\frac{1}{2z}| < 1\\ &= \sum_{n=0}^{\infty} (-2z)^{-n}(2z)^{-1}\\ &= \sum_{n=-\infty}^{\infty} \frac{1}{2}(-2)^{-n}z^{-n-1} u[n]\\ &\text{ let } k=n+1\\ &= \sum_{k=-\infty}^{\infty} \frac{1}{2}(-2)^{-k+1}u[k-1] z^{-k}\\ &\text{By comparison with the Z Transform definition...}\\ x[n] &= \frac{1}{2}(-2)^{-k+1}u[n-1]\\ \end{align} $

Ex. 5 Find the Inverse Z transform of the following signal

$ X(z)=\frac{-1}{z^2-4z-5}, \text{ ROC } 1<|z|<5 $

notice: ROC is type 3

Solution

$ \begin{align} X(z) &= \frac{-1}{z^2-4z-5}\\ &\text{ by partial fraction expansion}\\ &= \Big( \frac{1}{6} \Big)\Big( \frac{1}{z+1}+\frac{1}{5-z} \Big)\\ & \text{by infinite geometric series}\\ &= \Big( \frac{1}{6} \Big) \Bigg( \sum_{n=0}^{\infty} (\frac{1}{z})(\frac{-1}{z})^{n} + \sum_{m=0}^{\infty} (\frac{1}{5})(\frac{z}{5})^m \Bigg) \text{ if } 1<|z|< 5\\ &=\Big( \frac{1}{6} \Big) \Bigg( \sum_{n=-\infty}^{\infty} (-1)^n(z)^{-n-1}u[n] + \sum_{m=-\infty}^{\infty} (5)^{-m-1)}(z)^{m}u[m] \Bigg)\\ & \text{let } k=n+1, l=-m\\ &= \Big( \frac{1}{6} \Big) \Bigg( \sum_{k=-\infty}^{\infty} (-1)^{k-1}(z)^{-k}u[k-1] + \sum_{l=-\infty}^{\infty} (5)^{l-1)}(z)^{-l}u[-l] \Bigg)\\ & \text{using the linearity principle of Z transforms}\\ x[n] &= \frac{1}{6}(-1)^{n-1}u[n-1] + \frac{1}{6} (5)^{n-1)}(z)^{-n}u[-n] \end{align} $


Using Matlab to find Inverse Z Transforms [1]


Additional links


Questions, Comments - - -


Back to ECE438 Fall 2014

Alumni Liaison

Ph.D. on Applied Mathematics in Aug 2007. Involved on applications of image super-resolution to electron microscopy

Francisco Blanco-Silva